SAFETY SYSTEM FOR FOG AND ROCK FALLING - Deshmukh, Aishwarya B (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Climate challenge is a major environmental challenge today, with significant threats to environments, water resources, and economic constancycomplete. Today, safety and security are just a click away, and with such incidents happening, the security of public cannot be ignored. This system method is an example of the use of digital systems design to accomplish that goal, where the security and comfort of a people is the issue at hand. This device has been modelled such that it takes care of people and road. An automation system is needed over the areas where manual work is not suitable due to natural issues. As Programmable Logic Controller (PLC) is suitable to control system automatically without much manual supervision using sensors and devices for controlling the traffic. Here we are planning to develop a safety system to solve the accidental problems which occur due to natural cause such as fog, rockfall, etc. How to cite this article: Deshmukh AB, Suryawanashi DS. Safety System for Fog and Rock Falling. J Adv Res Appl Arti Intel Neural Netw 2019; 2(2): 28-30.